(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1999)
The paper presents investigation into the solution of multiple criteria decision making problems. Influence diagrams can be used as a formal model of decision making under risk.